The Importance of Social Cognition in Improving Functional Outcomes in Schizophrenia - Javed, Afzal; Charles, Asha (Frontiers in Psychiatry, 2018)
Social cognition has become recognized as an important driver of functional outcomes and overall recovery in patients with schizophrenia, mediating the relationship between neurocognition and social functioning. Since antipsychotic therapy targeting remission of clinical symptoms has been shown to have a limited impact on social cognition, there has been an increasing drive to develop therapeutic strategies to specifically improve social cognition in schizophrenia. We sought to review current evidence relating to social cognition in schizophrenia and its clinical implications, including interventions designed to target the core domains of social cognition (emotion processing, theory of mind, attributional bias, and social perception) as a means of improving functional outcomes and thereby increasing the likelihood of recovery. Relevant articles were identified by conducting a literature search in PubMed using the search terms “schizophrenia” AND “cognition” AND “social functioning”, limited to Title/Abstract, over a time period of the past 10 years. Current evidence demonstrates that schizophrenia is associated with impairments in all four core domains of social cognition, during the pre-first-episode, first-episode, early, and chronic phases of the disease, and that such impairments are important determinants of functional outcome. Interventions targeting the four core domains of social cognition comprise psychosocial approaches (social cognition training programs) and pharmacological therapies. Social cognition training programs targeting multiple and specific core domains of social cognition have shown promise in improving social cognition skills, which, in some cases, has translated into improvements in functional outcomes. Use of some psychosocial interventions has additionally resulted in improvements in clinical symptoms and/or quality of life. Pharmacological therapies, including oxytocin and certain antipsychotics, have yielded more mixed results, due in part to the confounding impact of factors including variation in receptor genetics, bioavailability, pharmacokinetics, and drug–drug interactions, and inconsistencies between study designs and medication dosages. Additional research is required to advance our understanding of the role of social cognition in schizophrenia, and to further establish the utility of targeted interventions in this setting.